Prospective Determination of Airway Response to Upper Airway Stimulation: A New Opportunity for Advanced Device Titration. (17th June 2020) - Jenks, Carolyn M.; Yu, Jason L.; Schmitt, Katherine A.; Schwab, Richard J.; Thaler, Erica R.
Abstract : Objectives/Hypothesis: Response to upper airway stimulation (UAS) is associated with the degree of airway opening during stimulation. UAS programming may affect this opening. The objective of this study was to examine airway changes in response to five different electrode configurations programmable within the Inspire UAS system. Study Design: Prospective single‐arm cohort study. Methods: Subjects who underwent UAS implantation were recruited for a prospective single‐arm cohort study during UAS device activation. Functional thresholds were recorded for all settings. Awake nasopharyngoscopy was performed to examine the retropalatal (RP) and retroglossal (RG) regions at rest and during activation with all settings at their functional thresholds. Cross‐sectional measurements were made by two blinded reviewers and reported as percent change in airway size. Results: Sixteen patients were included. The standard setting (+‐+) resulted in the greatest change in RP area in 43.8% of patients. An alternative setting resulted in greatest change in 56.2% of patients (‐‐‐ and o‐o in 18.8% each, ‐o‐ in 12.5%, and ‐+‐ in 6.3% of patients). Average response to all five settings was utilized to classify degree of palatoglossal coupling. Most patients had some enlargement (20%–70% change in RP area, 43.8%) or no enlargement (<20% change, 43.8%), whereas a minority of patients (12.5%) had marked enlargement (>70% change). RP and RG expansion were not correlated. Conclusion: Degree of RP expansion varied among patients and settings. Although the standard setting resulted in greatest RP change in a plurality of patients, over half had a greater response to an alternative setting. Future studies should address whether choice of setting based on RP expansion results in improved outcomes. Level of Evidence: 4 Laryngoscope, 131:218–223, 2021